Vacuolar Protein Sorting Genes in Parkinson's Disease: A Re-appraisal of Mutations Detection Rate and Neurobiology of Disease - Gambardella, Stefano; Biagioni, Francesca; Ferese, Rosangela; Busceti, Carla L.; Frati, Alessandro; Novelli, Giuseppe; Ruggieri, Stefano; Fornai, Francesco (Frontiers in Neuroscience, 2016)
Mammalian retromers play a critical role in protein trans-membrane sorting from endosome to the trans-Golgi network (TGN). Recently, retromer alterations have been related to the onset of Parkinson's Disease (PD) since the variant p.Asp620Asn in VPS35 (Vacuolar Protein Sorting 35) was identified as a cause of late onset PD. This variant causes a primary defect in endosomal trafficking and retromers formation. Other mutations in VPS genes have been reported in both sporadic and familial PD. These mutations are less defined. Understanding the specific prevalence of all VPS gene mutations is key to understand the relevance of retromers impairment in the onset of PD. A number of PD-related mutations despite affecting different biochemical systems (autophagy, mitophagy, proteasome, endosomes, protein folding), all converge in producing an impairment in cell clearance. This may explain how genetic predispositions to PD may derive from slightly deleterious VPS mutations when combined with environmental agents overwhelming the clearance of the cell. This manuscript reviews genetic data produced in the last 5 years to re-define the actual prevalence of VPS gene mutations in the onset of PD. The prevalence of p.Asp620Asn mutation in VPS35 is 0.286 of familial PD. This increases up to 0.548 when considering mutations affecting all VPS genes. This configures mutations in VPS genes as the second most frequent autosomal dominant PD genotype. This high prevalence, joined with increased awareness of the role played by retromers in the neurobiology of PD, suggests environmentally-induced VPS alterations as crucial in the genesis of PD.